2000
DOI: 10.1088/0022-3727/33/20/312
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum arc plasma jet interaction with neutral ambient gas

Abstract: Vacuum arc plasma jet (VAPJ) propagation in a neutral nitrogen atmosphere has been calculated numerically on the basis of a hydrodynamic description. It was assumed that the VAPJ was emitted isotropically from a point source located z0 = 20 mm in front of the entrance of a straight duct 100 mm in diameter in which an axial magnetic field of 0.02-0.05 T was imposed. Plasma densities of n0 = 1018 and 1019 m-3 and neutral gas densities nn0 = 0.001-0.1×n0 were used as initial conditions at the duct entrance. A thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The shock wave is characterized by a sharp increase of plasma density at the shock front, a decrease of directed ion velocity to beneath the sound velocity behind the shock front, and transfer of directed ion energy to thermal energy [20]. Shock formation for a vacuum arc plasma jet entering a background gas was described in the theoretical research by Gidalevich et al [21]. Meunier et al [22,23] observed a boundary between the regions of the metal vapour plasma jet and a background gas.…”
Section: Shock Front Formationmentioning
confidence: 99%
“…The shock wave is characterized by a sharp increase of plasma density at the shock front, a decrease of directed ion velocity to beneath the sound velocity behind the shock front, and transfer of directed ion energy to thermal energy [20]. Shock formation for a vacuum arc plasma jet entering a background gas was described in the theoretical research by Gidalevich et al [21]. Meunier et al [22,23] observed a boundary between the regions of the metal vapour plasma jet and a background gas.…”
Section: Shock Front Formationmentioning
confidence: 99%
“…The primary ion jet deceleration depends on the secondary ion or atom density. In the stationary the problem, 11 primary jet down to subsonic velocities such that a shock front appears. 16 In contrast, low secondary ions/atoms density causes only slightly decelerates the primary jet, and the plasma motion from the cathode remains continuous.…”
Section: Description Of the Problemmentioning
confidence: 99%
“…These values correspond to Mach number Mϭ13, thus the vacuum arc plasma jet ͑VAPJ͒ is considerably supersonic. The hydrodynamic description of the VAPJ was discussed previously, [7][8][9] as was the necessity of shock front formation, in multicathode VAPJs, 10 in the interaction with an ambient gas, [11][12][13] and in the interelectrode gap. 14 The VAPJ interacts with an obstacle in several practical devices, e.g., in vacuum arc plasma coating apparatus and circuit breakers.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them were mainly related to the study of elastic interactions between metallic ions and neutrals. [8][9][10][11][12] Other studies referred to inelastic interactions in the interelectrode region. From photon and ion emission studies, [13][14][15] it was concluded that charge-exchange reactions were the main channel for metallic ion losses, in a gas pressure ͑p͒ range of 10 −6 -10 −2 mbar.…”
Section: Introductionmentioning
confidence: 99%